Clinical profile of patients with acute kidney injury admitted in intensive care unit - Sah, Vijay Kumar; Prakash, Satyam (International Journal of Advances in Medicine, 2022)
Background: Acute kidney injury (AKI) is a frequent complication in critically sick patients admitted to the intensive care unit (ICU). The objective of this study was to assess the risk factors and clinical outcomes of AKI in patients admitted to a teaching hospital's intensive care unit. Methods: This prospective observational study was conducted in the department of internal medicine, Janaki Medical College, Janakpur, Nepal from June 2018 till May 2019. Adults (aged 18 years or more) diagnosed with AKI using RIFLE criteria and were either admitted in ICU with diagnosis of AKI or developed AKI after admission to ICU. AKI patients were classified as those who satisfied any of the RIFLE categorization criteria. Results: The most common presenting complaint was fever (77%). The most common etiology of AKI was sepsis (71%). Other causes of AKI were post-operative cases (16%) and alcoholic liver disease (13%). When classified as per RIFLE criteria, we classified 38 cases (31.9%) as ‘risk’, 53 (44.54%) as ‘injury’ and 28 (23.53%) as ‘failure’. The etiological classification of our patients to be significantly associated with RIFLE classification (p<0.01). However, we found the mortality not to be significantly associated with RIFLE classification (p=0.74). Conclusions: AKI classification should be used as a risk assessment tool towards the AKI's influence on the prognosis of ICU patients. Further study should investigate determining the death rate according to the RIFLE criteria in this region of Nepal.